The Ribosome Biogenesis Factor Ltv1 Is Essential for Digestive Organ Development and Definitive Hematopoiesis in Zebrafish - Zhang, Chong; Huang, Rui; Ma, Xirui; Chen, Jiehui; Han, Xinlu; Li, Li; Luo, Lingfei; Ruan, Hua; Huang, Honghui (Frontiers in Cell and Developmental Biology, 2021)
Ribosome biogenesis is a fundamental activity in cells. Ribosomal dysfunction underlies a category of diseases called ribosomopathies in human. The symptomatic characteristics of ribosomopathies often include abnormalities in craniofacial skeletons, digestive organs and hematopoiesis. Consistently, disruptions of ribosome biogenesis in animals are deleterious to embryonic development with hypoplasia of digestive organs and/or impaired hematopoiesis. In this study, ltv1, a gene involved in the small ribosomal subunit assembly, was knocked out in zebrafish by clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 technology. The recessive lethal mutation resulted in disrupted ribosome biogenesis, and ltv1Δ14/Δ14 embryos displayed hypoplastic craniofacial cartilage, digestive organs, and hematopoiesis. In addition, we showed that the impaired cell proliferation, instead of apoptosis, led to the defects in exocrine pancreas and hematopoietic stem and progenitor cells (HSPCs) in ltv1Δ14/Δ14 embryos. It was reported that loss-of-function of genes associated with ribosome biogenesis often caused phenotypes in a P53 dependent manner. In ltv1Δ14/Δ14 embryos, both P53 protein level and the expression of p53 target genes, Δ113p53 and p21, were up-regulated. However, knockdown of p53 failed to rescue the phenotypes in ltv1Δ14/Δ14 larvae. Taken together, our data demonstrate that ribosome biogenesis factor Ltv1 plays an essential role in digestive organs and hematopoiesis development in zebrafish in a P53 independent manner.